“Life Starts for Me Again.” The Social Impact of Psychology on Programs for Homeless People: Solidarity Networks for the Effectiveness of Interventions - Matulič-Domadzič, Virginia; Munté-Pascual, Ariadna; De Vicente-Zueras, Irene; León-Jiménez, Susana (Frontiers in Psychology, 2020)
The role of psychology on the improvement of people’s lives is consistent, attending the scientific literature review. More and more psychological studies, and other social sciences, are pointing out the importance of the quality of social interactions on physical and mental health and upon perceived wellbeing. When talking about homelessness, psychology has served these individuals mostly by informing intervention programs related to preventing and responding to substance’s use, healthcare, sexual risks or mental illnesses, key problems that also psychology has studied to be connected to homelessness. Such strategies, which traditionally were mostly centered on tackling the weaknesses that homeless people face, as the aforementioned, now are increasingly considering the role of the social support for achieving improvements. The aim of this study was to identify evidences on the importance of solidarity, being a specific kind of social support, as a key factor in the process of overcoming homelessness and associated substances’ abuse situation, identifying barriers and conditions, as well as approaching the impact of that solidarity on their general wellbeing, from the perspective of homeless subjects themselves. To achieve this aim, 20 life stories were conducted of people aged 35 to 70 years old, who had lived as homeless in a recent period of their lives and currently served by entities. The communicative methodology allowed deepening into the life stories of these individuals via egalitarian dialogue between the researchers and the participants. The results of the qualitative analysis show that a strong solidarity network has been crucial in the process of overcoming the participants’ homelessness situation and to tackle related circumstances (alcoholism and drugs’ abuse among others), what has had an impact in their general wellbeing and in the development of more solidarity attitudes. These findings are discussed in light of psychological knowledge and other social sciences literature on the importance of quality social environments to support positive developmental trajectories, considering the potential social impact of the intervention programs that contemplate the factor of solidarity in their implementation.